Iron-Binding Protein Degradation by Cysteine Proteases of Naegleria fowleri. (18th May 2015) - Martínez-Castillo, Moisés; Ramírez-Rico, Gerardo; Serrano-Luna, Jesús; Shibayama, Mineko
Abstract : Naegleria fowleri causes acute and fulminant primary amoebic meningoencephalitis. This microorganism invades its host by penetrating the olfactory mucosa and then traveling up the mesaxonal spaces and crossing the cribriform plate; finally, the trophozoites invade the olfactory bulbs. During its invasion, the protozoan obtains nutrients such as proteins, lipids, carbohydrates, and cationic ions (e.g., iron, calcium, and sodium) from the host. However, the mechanism by which these ions are obtained, particularly iron, is poorly understood. In the present study, we evaluated the ability of N. fowleri to degrade iron-binding proteins, including hololactoferrin, transferrin, ferritin, and hemoglobin. Zymography assays were performed for each substrate under physiological conditions (pH 7 at 37°C) employing conditioned medium (CM) and total crude extracts (TCEs) of N. fowleri . Different degradation patterns with CM were observed for hololactoferrin, transferrin, and hemoglobin; however, CM did not cause ferritin degradation. In contrast, the TCEs degraded only hololactoferrin and transferrin. Inhibition assays revealed that cysteine proteases were involved in this process. Based on these results, we suggest that CM and TCEs of N. fowleri degrade iron-binding proteins by employing cysteine proteases, which enables the parasite to obtain iron to survive while invading the central nervous system.